Tangled narratives of poverty in early childhood: othering, work, welfare and 'curveballs'. (1st October 2019) - Lyndon, Sandra
Abstract : Early years practitioners are integral to government policy on addressing child poverty in the UK. Drawing on findings from a qualitative study this paper seeks to contribute new understandings about how practitioners' narratives are shaped by discourses of poverty. Overall practitioners' understandings of poverty reflected a moral discourse of deserving and undeserving poor. However, the complexity of interconnections between morality, gender and motherhood (and fatherhood) reveals how understandings were also broad, nuanced and at times contradictory. The study highlights the need for further research into how understandings of poverty are formed together with the need for new narratives of poverty.